Perencanaan Tebal Perkerasan Kaku pada Jalan Nuansa Indah Selatan - Cempaka Biru Selatan, Kota Denpasar, Bali - Morim, Gruberth Dirk; Sumanjaya, Anak Agung Gede; Aryastana, Putu (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
Roads are one of the elements that play an important role in determining the development of an area, so it is very important to make a plan for the thickness of the road pavement. In Indonesia, there are generally two methods that are often used to plan the thickness of rigid pavement, namely the American Association of State Highway and Transportation Officials (AASHTO) 1993 and Manual Desain Perkerasan (MDP) 2017 methods. These two methods have several different parameters, where these differences in parameters are adjusted to the regulations that apply in Indonesia. Based on the condition of the existing road which already serves many commercial vehicles, the road can no longer support the load so the road becomes damaged. By looking at the problems that occur, a review is carried out in this planning, such as how to plan the thickness of the rigid pavement based on the AASHTO 1993 method and the MDP 2017 method. How much of the planned budget is needed to plan the thickness of the rigid pavement on the Nuansa Indah Selatan - Cempaka Biru Selatan road, Denpasar City, Bali and compared the two budget plan results to get more economical planning results. After calculating the thickness of the rigid pavement using the ASSHTO 1993 method, we obtained a plate thickness of 36.45 cm, lean concrete of 10 cm, Aggregate Foundation Layer Class A of 15 cm and soil stabilization of 30 cm, and the budget plan required is Rp 8,460,733,187,- whereas with the 2017 MDP method the pavement thickness is 27.5 cm, lean concrete is 10 cm, Aggregate Fondation Layer Class A is 15 cm and soil stabilization is 30 cm with the planned budget required is Rp 6,529,833,757,-. Based on the budget plan results obtained, a good choice to use on this road is to use the 2017 MDP method with a more economical price.